Development of a single column method for the separation of lipid- and protein-derived oligosaccharides. - Neville, D; Dwek, R; Butters, T (2009)
Fluorescent labeling of oligosaccharides with anthranilic acid (2-aminobenzoic acid; 2AA), or 2-aminobenzamide (2AB) permits the rapid, sensitive analysis of structures present in cells and tissues. Normal-phase (NP)/hydrophilic interaction chromatography (HILIC) is commonly used to separate fluorophore-derivatized oligosaccharides. Column elution is expressed as glucose units (GU) following calculation of relative retention when compared to an external glucose oligomer standard. However, there is significant overlap between sialylated and neutral oligosaccharides. Normal-phase anion-exchange (NP-AE) HPLC can separate differing classes of oligosaccharides according to the number of charged residues, but relative retention times in GU cannot be calculated across the entire gradient. We have overcome this difficulty by use of a Dionex AS11 column that combines both hydrophilic interaction and anion-exchange chromatographies, termed HIAX, which enables the calculation of GU values for oligosaccharides that carry sialylated or other negatively charged groups. The same method may also be employed for 2AB and other fluorophore-labeled oligosaccharides. Additionally, the same HPLC eluants are used for the differing HPLC columns. Therefore, analysis of HILIC- or HIAX-separated fluorophore-labeled oligosaccharides can be performed using a single HPLC system with a single set of eluents following a simple column change.